Educational Needs Assessment and Educational Program Planning with the Developing a Curriculum Model in Shiraz University of Medical Sciences Iran - Mohammad Reza Dehghani; Solmaz Zare; Leila Bazrafkan; Mitra Amini; Javad Koujori; Ali Asghar Hayat; Parisa Nabeiei (Kerman University of Medical Sciences, 2014)
Background & Objective: One of the most practical and most recognized methods of needs assessment and educational planning is the Developing a Curriculum (DACUM) model Today this model is employed as a creative and effective method in occupation or profession analysis   Methods: In the present study during 3 workshops in 2 days and by using DACUM method educational needs assessment and occupation analysis was performed on the educational administrators (assistant dean for educational affairs in schools heads of departments and vicechancellors for educational affairs in educational hospitals) of Shiraz University of Medical Sciences Iran Results of this process served as foundational elements to planning training programs for the educational administrators   Results: The workshop resulted in the identification of 6 duties and 51 tasks for vicechancellors for educational affairs in educational hospitals 9 duties and 81 tasks for assistant dean for educational affairs in schools 16 duties and 98 tasks for heads of departments Moreover a list of associated knowledge skills tools equipment supplies materials used and desirable worker traits for this occupational category was provided Then using results of panels a questionnaire was designed in order to identify the importance learning difficulty and frequency of performance of duties and tasks In addition lists of general knowledge worker behaviors tools equipment and supplies and future trends and concerns were verified by respondents and the DACUM committee   Conclusion: Finally based on the verified results and review of the literature a training program based on goals context and method of performance and evaluation was prepared in order to be used by educational administrators of Shiraz University of Medical Sciences